2020
DOI: 10.1186/s12889-020-09427-5
|View full text |Cite
|
Sign up to set email alerts
|

The physical activity at work (PAW) study protocol: a cluster randomised trial of a multicomponent short-break intervention to reduce sitting time and increase physical activity among office workers in Thailand

Abstract: Background High levels of sedentary behaviour (SB) are associated with non-communicable diseases. In 2016, the estimated total healthcare expenditure from physical activity (PA) in Thailand added up to $190 million in international dollars. The challenge to reduce SB and increase PA among office workers is more urgent now than ever as Thailand is transforming itself from a predominantly rural country to an increasingly urban one. This study will investigate the effectiveness of a multicomponent sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Most rural Thais are occupied in agricultural activities [43] that require PA in physically demanding transportation and farming. By contrast, urban Thais rely more on the motorized transportation and are employed in jobs that involve sitting in front of a computer terminal for much of the work day [44]. During the pandemic, the government's Covid-19 containment policy was also more strictly enforced in cities, given the fact that more densely populated settlements provide a greater opportunity for easy spread of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Most rural Thais are occupied in agricultural activities [43] that require PA in physically demanding transportation and farming. By contrast, urban Thais rely more on the motorized transportation and are employed in jobs that involve sitting in front of a computer terminal for much of the work day [44]. During the pandemic, the government's Covid-19 containment policy was also more strictly enforced in cities, given the fact that more densely populated settlements provide a greater opportunity for easy spread of infection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Thailand, the national Health Promotion Foundation has recently commissioned the 'Physical Activity at Work' research programme to help address the increasing rates of SB in the population. 41 Our findings will also further inform the implementation of workplace interventions in countries where guidelines or nationwide initiatives to reduce SB or increase PA already exist, such as Australia, 42 UK 43 or Singapore. 44 Finally, this RoR will also allow potential research gaps to be identified, so that the design of future studies can be better informed.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, inactivity should be considered a major problem in public health because the majority of adults in industrialized and undeveloped countries do not meet health-related guidelines for physical activity (6,12). Workplace health promotion programs are effective means for the promotion of healthy behaviors (13). This study was accomplished to determine the effect of an educational intervention to promote physical activities among employees.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, inactivity must be considered the main health problem for societies (12). Workplace health promotion has generally focused on promoting employees' health through the decrease of individual risk-related behaviors (12,13). Therefore, employees seem to be vital a population to promote the maintenance of adequate physical activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation